(untitled) (Brazilian Journal of Radiation Sciences, 2019)
The present research proposal aimed to measure absorbed dose in a thorax phantom with synthetic breasts provided by an Intensity-Modulate Radiation Therapy (IMRT) protocol in an arbitrary RT center. As methods, a thorax simulator was prepared by the Ionizing Radiation Research Group (NRI) and radiochromic films were used for dose measurements. Tomographic images were taken at NRI phantom. Expositions were procedure in the Elektra 6MV LINAC. Hypofractionated regime was considered with a dose fraction of 2,7Gy in 16 fractions at the prescribed dose of 43.2 Gy at 95% of PTV. The dose comparison from the treatment planning system (TPS), Xio (Elekta) and from the experimental data was performed. The internal two-dimensional dose maps in the breast, at the skin on the left and contra-lateral breasts, heart and lungs. The measurements showed that the internal mean doses taken at the synthetic breast presented mean dose above the prescribed dose. Moreover, in general, doses to organs at risk (OARs) were within the Memorial Sloan Kettering Cancer Center (MSKCC) criteria. The non-full reproduction of the build-up region in the films had occurred due to the assymetrical positioning of the films in the inner breast, in the addition to their non-constant distance from the skin. Hot regions were present, may be due to the beam angulation chosen and the increase of MUs in the IMRT plane. As conclusions, the films can supply details and information that TPS does not provide. Assertiveness in clinical IMRT protocols can improve the prognosis and effectiveness of breast cancer treatment bring-ing possible clinical benefits.